Determinación de colorantes sintéticos en bebidas industriales no alcohólicas comercializadas en la ciudad de trujillo en 2013. - Alva Ibáñez, Víctor Eduardo (2014)
In this research work synthetic colorants in non-alcoholic drinks sold in Trujillo City in 2013 were characterized. Eighteen samples of beverages purchased in the local market were analyzed. The synthetic dyes were initially characterized qualitatively by the Arata – Possetto method and subsequently extracted by a modification of the method. The structure of synthetic colorants was verified by infrared spectroscopy. The concentration of tartrazine in the yellow drinks was determined by UV-VIS spectroscopy. The results indicate the presence of artificial colorants allowed by DIGESA, in accordance with US FDA regulations, with the only exception of the colorant E123 (amaranth), which is not allowed by the standard. The IR spectroscopy data are consistent with the structure of the dyes indicated in each sample. In all cases, the concentrations of tartrazine are within the allowed range.